Environmental Impact 2012
DOI: 10.2495/eid120181
|View full text |Cite
|
Sign up to set email alerts
|

The analysis of urban travellers’ latent preferences to explain their mode choice behaviour

Abstract: Our research aims to explore the impact of latent variables, mirroring urban travellers' attitudes and perceptions, on the individual decision making process regarding the mode of transport. The paper describes the first results of an ongoing research activity, which derive from a pilot study conducted in Palermo, the capital of the Sicilian Region (in the south of Italy), and demonstrate that policy makers, in designing a socially desirable and environmentally sustainable urban mobility system, should take in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 2 publications
(1 reference statement)
0
1
0
Order By: Relevance
“…The area is characterized by low travel demand; it is spatially and temporally dispersed, and served by low-quality public transport services-this makes microtransit a viable option for improving the accessibility and quality of public transport in the study area. Moreover, a previous study conducted in Palermo [27] showed that the time spent walking to stops is more bothersome than longer in-vehicle times, from citizens' perspectives. Therefore, introducing a transport service able to reduce walking times to stops is a significant way to improve the attractiveness of the public transport in the study area.…”
mentioning
confidence: 98%
“…The area is characterized by low travel demand; it is spatially and temporally dispersed, and served by low-quality public transport services-this makes microtransit a viable option for improving the accessibility and quality of public transport in the study area. Moreover, a previous study conducted in Palermo [27] showed that the time spent walking to stops is more bothersome than longer in-vehicle times, from citizens' perspectives. Therefore, introducing a transport service able to reduce walking times to stops is a significant way to improve the attractiveness of the public transport in the study area.…”
mentioning
confidence: 98%
“…To estimate both the weights and the discrimination thresholds, we have searched for the values of these coefficients that maximise the ability of the simulation model to reproduce the similarity relations found within a sample of road signs by a sample of individuals [26,27,28,29,30,31,32].…”
Section: Synthesizing the Graphic Difference Measuresmentioning
confidence: 99%